PARETO CLAIM SEVERITY DISTRIBUTION AND DETERMINATION OF OPTIMAL RETENTION - PERMATA INDAH (NIM : 20813006); Pembimbing : Khreshna I.A. Syuhada, M.Sc, Ph.D, NOVI
One of the risk form in the insurance contract that the claims should be covered by an insurer. Generally, data of the claim severity are skewed to right and heavy tailed. In this thesis, the candidate distribution in accordance with data claim severity is a Pareto distribution. The values of claim severity that are not able to be paid by the insurance company will be shared with another insurer is called reinsurer. When we devided claim severity on the reinsurance contract, we need a boundary which is a risk measure. In actuarial science this risk measures is called retention. Retention will be determined through one of the risk measure that is quantile based Value-at-Risk (QVaR) and expectile based Value-at-Risk (EVAR). Analytically and numerically EVaR risk measure is coherent and has a better value than QVaR.